2019
DOI: 10.1097/md.0000000000016872
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin axis blockade, acute kidney injury, and perioperative morbidity in patients undergoing colorectal surgery

Abstract: Patients undergoing surgery and taking angiotensin converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB) are susceptible to complications related to intraoperative hypotension. Perioperative continuation of such medications in patients undergoing colorectal surgery may be associated with more harm than benefit, as these patients are often exposed to other risk factors which may contribute to intraoperative hypotension. Our objectives were to assess the incidence and severity of postinducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Many, but not all, of the available studies suggest that PO-AKI defined by oliguria alone is more common than PO-AKI defined by changes in serum creatinine levels 26 , 37 39 . In a study of PO-AKI after non-cardiac surgery, the incidence of AKI increased from 8% to 64% if urine output was included in the definition 37 .…”
Section: Pathophysiology and Epidemiologymentioning
confidence: 99%
“…Many, but not all, of the available studies suggest that PO-AKI defined by oliguria alone is more common than PO-AKI defined by changes in serum creatinine levels 26 , 37 39 . In a study of PO-AKI after non-cardiac surgery, the incidence of AKI increased from 8% to 64% if urine output was included in the definition 37 .…”
Section: Pathophysiology and Epidemiologymentioning
confidence: 99%
“…Therefore, it seems logical that withholding these agents in the perioperative period may be effective at reducing postoperative AKI incidence. However, this is not borne out by recent prospective and retrospective studies (34,35), indeed the STARsurg collaborative concluded that withholding ACEis or ARBs did not demonstrate a protective effect against the development of postoperative AKI within the general surgical population (36). Given that many patients are placed on ACEis or ARBs for both their cardioprotective and kidneyprotective features, a risk-benefit analysis of continuing these medications in the perioperative period should be taken on an individualized basis, as should their reintroduction postoperatively.…”
Section: Preoperative Factorsmentioning
confidence: 99%
“…Though a retrospective cohort study of 1,358 adults revealed that preoperative use of ACEIs/ARBs associated with an increased risk for AKI after cardiovascular surgery (Arora et al, 2008), a newer prospective cohort study of 1,594 adults revealed that preoperative ACEIs/ARBs usage was associated with functional but not structural AKI after cardiac surgery (Coca et al, 2013). However, some studies showed that ACEIs/ARBs were not associated with postoperative AKI (Tagawa et al, 2015;Bonavia et al, 2019), and a study suggested that preoperative ACEIs/ARBs are associated with reduced postoperative AKI requiring dialysis and even reduced mortality (Shah et al, 2014). The risk and benefit of perioperative use of ACEIs/ARBs remained uncertain.…”
Section: Introductionmentioning
confidence: 99%